ELECTRIC AND MAGNETIC FIELDS DUE TO DIRAC PARTICLES IN FRW SPACETIME - Dhungel, P R; Sharma, S K; Khanal, U (Scientific World, 2015)
Some solutions of the Maxwell equations with Dirac particles for the source in FRW spacetime are discussed. The Green’s function of the equation for the radial component of the Maxwell fields, Fr? and F?? is solved. Green’s function is found to reduce to that of Minkowskian spacetime in the appropriate limit. Also, the Lienard-Wiechert type solution is derived. Also, the solutions with the Dirac particle current is also presented. It is found that the Fr? is composed of even angular momentum states while the odd states constitute F??. Scientific World, Vol. 12, No. 12, September 2014, page 1-4